2018
DOI: 10.5792/ksrr.18.017
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Excision of Medial Knee Plica: A Meta-Analysis of Outcomes

Abstract: PurposeA meta-analysis was performed to assess the outcomes following surgical intervention for medial knee plica.Materials and MethodsA literature search of Medline, EMBASE, CINAHL and Cochrane CENTRAL was performed using relevant key words. The primary outcome was patient-reported postoperative scores of “good” and “excellent”. Meta-analyses were performed using a random effects model.ResultsThe literature search identified 731 articles. After removing duplicates and those not meeting the inclusion criteria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…The presence of a type C and D medial parapatellar plicae has been associated with conservative treatment unresponsiveness, longer duration of symptoms, and associated patellofemoral cartilage injuries such as the patient presented in the current case report [10]. A meta-analysis by Gerrard et al [5] reported favorable patient outcomes in medial parapatellar plica syndrome patients undergoing arthroscopic excision after failed conservative treatment. In the present study, arthroscopic media plica excision led to complete symptoms resolution at one month postoperatively, and the patient was then allowed to return to full activity, with no recurrence at the last follow-up, one year postoperatively.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…The presence of a type C and D medial parapatellar plicae has been associated with conservative treatment unresponsiveness, longer duration of symptoms, and associated patellofemoral cartilage injuries such as the patient presented in the current case report [10]. A meta-analysis by Gerrard et al [5] reported favorable patient outcomes in medial parapatellar plica syndrome patients undergoing arthroscopic excision after failed conservative treatment. In the present study, arthroscopic media plica excision led to complete symptoms resolution at one month postoperatively, and the patient was then allowed to return to full activity, with no recurrence at the last follow-up, one year postoperatively.…”
Section: Discussionmentioning
confidence: 65%
“…However, the most accepted theory establishes the development of menisci, cruciate ligaments, and a partitioned joint cavity in the eight-week fetus, with the subsequent fusion of the joint knee compartments and resorption of the synovial septum by the end 12th week. In cases of incomplete resorption of the synovial septum, residual mesenchymal tissues result in the knee plicae [5,6,12,13,19,26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations